High Fat Diet Dysbiotic Mechanism of Decreased Gingival Blood Flow - Stanisic, Dragana; Jeremic, Nevena; Majumder, Suravi; Pushpakumar, Sathnur; George, Akash; Singh, Mahavir; Tyagi, Suresh C. (Frontiers in Physiology, 2021)
The gut microbiome has a very important role in human health and its influence on the development of numerous diseases is well known. In this study, we investigated the effect of high fat diet (HFD) on the onset of dysbiosis, gingival blood flow decreases, and the periodontal matrix remodeling. We established a dysbiosis model (HFD group) and probiotic model by Lactobacillus rhamnosus GG (LGG) treatment for 12weeks. Fecal samples were collected 24h before mice sacrificing, while short chain fatty acids (SCFA) analysis, DNA extraction, and sequencing for metagenomic analysis were performed afterwards. After sacrificing the animals, we collected periodontal tissues and conducted comprehensive morphological and genetic analyses. While HFD reduced Bacteroidetes, SCFA, and gingival blood flow, this type of diet increased Firmicutes, lipopolysaccharide (LPS) binding protein, TLR4, pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), matrix metalloproteinases (MMP-2 and MMP-9) expression, and also altered markers of bone resorption (OPG and RANKL). However, LGG treatment mitigated these effects. Thus, it was observed that HFD increased molecular remodeling via inflammation, matrix degradation, and functional remodeling and consequently cause reduced gingival blood flow. All of these changes may lead to the alveolar bone loss and the development of periodontal disease.